Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.pmedr.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

No-cost gym visits are associated with lower weight and blood pressure among non-Latino black and Latino participants with a diagnosis of hypertension in a multi-site demonstration project

Abstract: Well documented, persistent racial/ethnic health disparities in obesity and hypertension in the US demonstrate the continued need for interventions that focus on people of color who may be at higher risk.We evaluated a demonstration project funded by the CDC's Racial/Ethnic Approaches to Community Health (REACH) program at four federally qualified health centers (FQHC) and YMCA fitness and wellness centers in Boston. No-cost YMCA memberships were offered from June 2014 to June 2015 to non-Latino black and Lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…For example, a U.S. study showed that no-cost gym visits are associated with lower weight and blood pressure among African American and Latinx participants who have hypertension. 39 In Dakar, Senegal, the installation of workout equipment on beaches led to the rise of a social fitness movement that has sustained momentum for more than 20 years. Localized programs grew from that movement, such as group exercise classes where participants also socialize, encourage, and connect.…”
Section: A Preferable Future That Shifts the Focusmentioning
confidence: 99%
“…For example, a U.S. study showed that no-cost gym visits are associated with lower weight and blood pressure among African American and Latinx participants who have hypertension. 39 In Dakar, Senegal, the installation of workout equipment on beaches led to the rise of a social fitness movement that has sustained momentum for more than 20 years. Localized programs grew from that movement, such as group exercise classes where participants also socialize, encourage, and connect.…”
Section: A Preferable Future That Shifts the Focusmentioning
confidence: 99%